(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
A new trend of social media is shaping the future of business environment according to its operations. It has also helped businesses to increase their worthiness, cultivate strategic partnerships and increase their contact with customers and suppliers. It has become important for business owners and marketers to understand how social media works as a communication and marketing tool. The study focused on establishing the effect of social media on the growth of SMEs in Bihar. The study used descriptive research design. Questionnaires were administered on 206 SMEs in Bihar, with the respondents being either the owners or managers. Cluster sampling was used to divide the population of interest and then simple random probability sampling technique was used to further identify the specific businesses to be used for the study. Both quantitative and qualitative data was collected and then analyzed using SPSS. The study established that social media tools offer greater market accessibility and CRM, which in turn have a significant impact on the growth of SMEs. It revealed that geographical barriers can be broken down by the use of social media tools.